Surfactant-Assisted Extraction of Trace Metals from Sedimentary Rocks as a Green Alternative to Acid Digestion Prior to ICP-OES Determination - Fagbemi, Omolara; Olajide, Bambo; Oluwaniyo, Ojo; Akinlua, Akin (FUDMA Journal of Sciences, 2026)
A surfactant-assisted extraction method was investigated for the determination of trace metals in sedimentary rock matrices prior to inductively coupled plasma optical emission spectrometry (ICP-OES) analysis. The approach employs non-ionic surfactants as extraction media to reduce dependence on conventional acid digestion while facilitating metal mobilization from the solid matrix. Triton X-100 and polyoxyethylene lauryl-10-ether were applied for the extraction of Ni, Pb, Zn, Mn, and Co under optimized conditions. The method exhibited good calibration linearity (R² > 0.999), limits of detection ranging from 0.08 to 0.42 μg g⁻¹, and relative standard deviations below 5%. Moderate spike recoveries of 72–85% were obtained, reflecting the challenges associated with analyte release from complex geological matrices. Comparison with EPA 3050B partial acid digestion yielded higher measured concentrations of Ni, Pb, Zn, and Mn in the surfactant-assisted extracts. While these differences suggest that the two methods access metals differently within the matrix, further studies are required to establish the underlying extraction mechanisms and to assess potential matrix-related effects. In addition, the proposed method substantially reduces the consumption of strong mineral acids, supporting the principles of green analytical chemistry. The results demonstrate the feasibility of surfactant-assisted extraction for trace metal determination in sedimentary rocks; however, validation using certified reference materials is required before definitive conclusions regarding method accuracy can be drawn.